STUDYING THE POSSIBILITIES OF THE INFRARED LASER WITH (λ)904 FOR TREATMENT OF BONE RESORPTION OF DENTAL IMPLANTS IN PROCESS OF OSSEOINTEGRATION - Hristina Lalabonova; Hristo Daskalov (Peytchinski Publishing, 2014)
The objective of this study is to establish the possibilities of the infrared laser with (λ) 904 for treatment of bone resorptionof bone implants in the process of osseointegration. Material and methods: The osseointegration process of 167 implants was radiologically evaluated between the first and the second surgical stage. In nine was established bone resorption reaching the implant screw. For the treatment was used infrared laser with (λ) 904 nm. Six procedures were performed, every other day, with a dose of 3-4 J/ cm2. Results: The x-ray tests done about three months after the treatment showed restoration of the bone resorption. Conclusion: In diagnosed bone resorption of implants in process of osseointegration, the application of infrared lasertherapy with (λ) 904 nm, with protocol of six sessions every other day, with dose 3-4 J/ см2per session, recovers the bone structure.